Effect Promotion Price and The Quality of Interest to Visit Soekarno Cave Pasongsongan Sumenep During Pandemic Covid 19 - RM. Maliki; Moh. Kurdi (The Academy Of Management and Business, 2022)
Tourism is one of the contributors to state revenue, since the COVID-19 pandemic, tourism sector income has decreased drastically. Because it aims to prevent the transmission of the covid 19 virus. Soekarno. Since the covid 19 pandemic around the world, visitors who come to Soekarno Cave have decreased. Various efforts have been made with the health protocols that have been set by the government. This study aims to determine and analyze the influence of promotional strategies, prices, and service quality on interest in visiting Soekarno Cave during the covid 19 pandemic. The population in this study were visitors to Soekarno Cave and the sample used in this study was 60 samples with the accidental sampling method. The analysis technique used is multiple linear analysis, taking into account the quality test requirements of the instrument, namely the validity and reliability test, as well as the classical assumption test, namely normality, multicollinearity test, heteroscedasticity test, and autocorrelation test. The results of this study obtained (X1) that the promotion did not significantly affect the interest in visiting, (X2) the price had a significant effect on the interest in visiting, and (X3) the quality of service had a significant effect on the interest in visiting. It is known that the value of R Square is (0.332) which means that the promotion strategy, price, and service quality affect the interest in visiting by 33.2% and the remaining 66.8.% is influenced by other variables not examined in this study.